2015
DOI: 10.1080/00103624.2015.1005225
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-Sorption Characteristics and Phosphorus Buffer Coefficients of Some Important Soils in Lao PDR

Abstract: An estimated 97 percent of the soils in Laos are characterized by low phosphorus (P). This characteristic, together with high acidity, constrains food crop production. The P status, sorption, and associated properties were evaluated for fifteen important agricultural soils from the uplands. Soil pH values ranged from 4.5 to 5.9. Soil organic carbon (C) varied from 7.0 to 22.9 g kg −1 . Soil clay varied from 179 to 709 g kg −1 . The cation exchange capacity (CEC) also varied from 4.30 to 32.1 cmol c kg −1 . Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Other researchers in Laos have previously identified soil phosphorus (P) as being among the nutrients that most limiting growth of rice in both uplands soils of Laos [3] [4] as well as in lowland soils [5]. A subsequent study also carried out by the senior author of this manuscript confirmed and quantified the extensive P deficiency in Lao uplands [6].…”
Section: Introductionsupporting
confidence: 59%
“…Other researchers in Laos have previously identified soil phosphorus (P) as being among the nutrients that most limiting growth of rice in both uplands soils of Laos [3] [4] as well as in lowland soils [5]. A subsequent study also carried out by the senior author of this manuscript confirmed and quantified the extensive P deficiency in Lao uplands [6].…”
Section: Introductionsupporting
confidence: 59%